2008
DOI: 10.1113/jphysiol.2008.162503
|View full text |Cite
|
Sign up to set email alerts
|

STIM1–Orai1 interactions and Orai1 conformational changes revealed by live‐cell FRET microscopy

Abstract: Ca2+ entry through store-operated Ca 2+ release-activated Ca 2+ (CRAC) channels initiates key functions such as gene expression and exocytosis of inflammatory mediators. Activation of CRAC channels by store depletion involves the redistribution of the ER Ca 2+ sensor, stromal interaction molecule 1 (STIM1), to peripheral sites where it co-clusters with the CRAC channel subunit, Orai1. However, how STIM1 communicates with the CRAC channel and initiates the subsequent events culminating in channel opening is unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
283
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(308 citation statements)
references
References 40 publications
21
283
4
Order By: Relevance
“…We also observe no changes of 2-APB on endogenous STIM1 puncta formation. In contrast, 2-APB was reported to prevent STIM1 puncta (22,25), although a recent study revealed this effect occurs only with extended 2-APB exposure (35). Importantly, in the same study, FRET analysis between coexpressed full-length STIM1 and Orai1 revealed that 50 M 2-APB could induce an increased association between the proteins after store depletion, but it did not visibly alter STIM1 or Orai1 in puncta.…”
Section: Resultsmentioning
confidence: 79%
“…We also observe no changes of 2-APB on endogenous STIM1 puncta formation. In contrast, 2-APB was reported to prevent STIM1 puncta (22,25), although a recent study revealed this effect occurs only with extended 2-APB exposure (35). Importantly, in the same study, FRET analysis between coexpressed full-length STIM1 and Orai1 revealed that 50 M 2-APB could induce an increased association between the proteins after store depletion, but it did not visibly alter STIM1 or Orai1 in puncta.…”
Section: Resultsmentioning
confidence: 79%
“…Attention has focused mainly on ORAI1 channels with the SCID mutation R91W (2) or with the experimental replacements R91V, R91L, or R91F (35), which fail to carry current upon store depletion even though the proteins are at the cell surface and interact with STIM1 (35)(36)(37)(38). R91 itself is not essential, as evidenced by the normal currents carried by R91E and R91G channels (35), and therefore the defect in the R91W channel has been interpreted as interference by the bulky tryptophan side chain with channel gating or with ion flux through the pore (35)(36)(37)(38). Other substitutions of interest are R91T, which reduces the amplitude of whole-cell currents compared to wild-type ORAI1; and S89G/S90G, which increases currents (35).…”
Section: Discussionmentioning
confidence: 99%
“…ORAI1 has been assumed to act in concert with STIM1 (10,19,20), activating inward Ca 2ϩ currents after store depletion. We and others have recently provided evidence that store depletion leads to a dynamic coupling of STIM1 to ORAI1 (21)(22)(23), probably involving the putative coiled-coil domain in the C terminus of ORAI1 (22). Furthermore, the C terminus of STIM1 has been established as the key fragment for CRAC as well as ORAI1 activation because its expression alone, without the necessity to deplete ER store, is sufficient for constitutive current activation (18,22,24).…”
Section: Store-operated Camentioning
confidence: 99%